Teaching material based on biomechanical evidence: 'high-jump hurdles' for improving fundamental motor skills - Otsuka Mitsuo; Otomo Satoshi; Isaka Tadao; Kurihara Toshiyuki; Akutsu Chihiro (Sciendo, 2015)
Study aim: the purpose of this study has been to develop teaching materials to help improve junior high school students' fundamental ability to repeatedly run and jump with a high and far-reaching travelling motion and to confirm the effectiveness of a new unit using teaching materials that are experimental in comparison to a conventional unit.